2018
DOI: 10.11648/j.ajp.20180403.15
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sectional Survey of Care Seeking For Acute Respiratory Illness in Children Under 5 Years in Rural Kenya

Abstract: Acute respiratory infection (ARI) is a leading cause of childhood morbidity and mortality in developing countries. In Kenya, diagnosis and treatment of ARI remains predominantly health facility based. This presumes that caretakers can recognize ARI symptoms promptly and make a decision to take the child to an appropriate health facility for treatment. Unfortunately, these presumptions have not been assessed. This study sought to establish determinants of health care seeking among caretakers of children under f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
2
9
2
Order By: Relevance
“…The present study revealed that the percentage of mothers delayed to seek health care for their pneumonia ill under-five children attending at Bahir Dar city hospitals was 48.6% (95%CI:45.8,54.7). This finding was lower than the studies conducted in Kenya (62.1%) and Tanzania (55.4%) [14, 17]. The possible explanation might be a difference in socio- demographic characteristics like study setting and lifestyle.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The present study revealed that the percentage of mothers delayed to seek health care for their pneumonia ill under-five children attending at Bahir Dar city hospitals was 48.6% (95%CI:45.8,54.7). This finding was lower than the studies conducted in Kenya (62.1%) and Tanzania (55.4%) [14, 17]. The possible explanation might be a difference in socio- demographic characteristics like study setting and lifestyle.…”
Section: Discussioncontrasting
confidence: 73%
“…Similarly, 66 % of mothers who used traditional medicine were delayed to seek healthcare. This proportion was very high compared to the study conducted in Kenya, 2.3% [14]. This might be related to the cultural differences of the communities.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Studies in Ethiopia, Kenya, and Bangladesh showed delays in care-seeking for children with pneumonia in 48.6%, 62.1%, and 52.7% of cases respectively [ 17 19 ]. In these studies, the factors that were associated with delay in seeking care included; the cost of services or treatment, transportation costs and loss of wages incurred while taking the child to a hospital, sex of caregiver and social norms, insufficient knowledge of danger signs and illness severity, previous experiences with health services, child’s age, and sex, maternal education, maternal employment status, decision-making status, use of self-prescribed antibiotics, gender roles, rural residence, perceived quality of health services, cultural beliefs about the illness and perceived illness severity [ 11 , 18 21 ].…”
Section: Introductionmentioning
confidence: 99%